2010
DOI: 10.3945/jn.109.116822
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Growth Restriction Modifies the Developmental Pattern of Intestinal Structure, Transcriptomic Profile, and Bacterial Colonization in Neonatal Pigs

Abstract: Neonates with intrauterine growth restriction (IUGR) are prone to suffer from digestive diseases. Using neonatal pigs with IUGR, we tested the hypothesis that IUGR may induce alterations in the developmental pattern of intestinal barrier and thereby may be responsible for IUGR-associated increased morbidity. Piglets with a birth weight near the mean birth weight (+/-0.5 SD) were identified as normal birth weight (control) and piglets with a mean -2 SD lower birth weight (-30%) were defined as piglets with IUGR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
96
2
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(110 citation statements)
references
References 45 publications
4
96
2
7
Order By: Relevance
“…Recent clues from transcriptomic profiles of the intestine have revealed molecular evidence of IUGR-induced impairment in intestinal growth that may result from changes in the cell proliferation-apoptosis balance (D'Inca et al, 2010). For the control of cell apoptosis, p53 has received significant attention (Miyashita and Reed, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent clues from transcriptomic profiles of the intestine have revealed molecular evidence of IUGR-induced impairment in intestinal growth that may result from changes in the cell proliferation-apoptosis balance (D'Inca et al, 2010). For the control of cell apoptosis, p53 has received significant attention (Miyashita and Reed, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…IUGR has been primarily attributed to placental insufficiency during the intrauterine phase (Wu et al, 2006), and can be regarded as the failure of a fetus to reach its genetic growth potential. The small intestine, which is the portal for absorption of virtually all nutrients into the blood stream, can be dramatically altered in IUGR neonates (D'Inca et al, 2010). This, along with compromised intestinal growth and development, can lead to atrophy of the intestine and impairment of nutrient absorption and utilization (Weaver et al, 1991;Baserga et al, 2004;Bjornvad et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a recent study has shown that enteral administration of ghrelin in neonatal piglets influenced both intestinal growth and intestinal epithelial cell turnover (Slupecka et al, 2012). As IUGR induces intestinal growth impairment (D'Inca et al, 2010b), the knowledge of an altered gastric GC distribution in the SGA piglets may be used for the preparation of milk formulas for neonates suffering from an insufficient development of the gastrointestinal system.…”
Section: Discussionmentioning
confidence: 99%
“…The high morbidity associated with IUGR in humans and animals can be attributed to an impaired development of various organs, such as those of the gastrointestinal system (D'Inca et al, 2010b). Consequently, IUGR neonates are prone to food intolerance, decreased fat absorption and digestive diseases during early postnatal life (Xu et al, 1994;Lee et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation